Digital Hermeneutics and the Politics of Exclusion: Deconstructing Salafi Interpretations of al-Walā’ wa al-Barā’ on Indonesian YouTube - Bakar, Abu; Billah, Rodina; Dimyathi, Muhammad Afifudin; Mahzumi, Fikri (ADDIN, 2026)
The article investigates the digital contestation of al-Walā’ wa al-Barā’ (loyalty and disavowal) by Indonesian Salafi networks, focusing on YouTube channel of Rodja TV. This qualitative study employs Norman Fairclough’s Critical Discourse Analysis (CDA) to examine selected da‘wah (lecture) videos on Rodja TV’s YouTube channel through three analytical dimensions: textual analysis, discursive practice, and sociocultural practice. The study demonstrates how digital platforms transform complex Islamic theology into a rigid, binary ideological instrument. The findings reveal that digital exegesis systematically simplifies authoritative tafsīr (exegesis), leveraging pejorative labeling and algorithmic enclaves to construct an exclusive identity while marginalizing the “others”. By contrasting these digital narratives with the maqāṣidī (objectives) interpretations of Ibn Āshūr and Wahbah al-Zuḥaylī, this study reveals a profound deculturation and mediatization of religion. This article contributes to Islamic studies and digital sociology by illuminating how online Salafi discourse facilitates “cognitive radicalization” and affective polarization, threatening multiculturalism in a democratic society. Ultimately, it underscores the critical need to disseminate maqāsidī (objective)-oriented counter-narratives to dismantle the exclusivist echo chamber and restore religion’s role in fostering inclusive social cohesion.